2021
DOI: 10.1080/09638237.2021.1922651
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processes associated with emotional disorders: implications for efficient psychological treatments

Abstract: Background: Emotional disorders are the most prevalent worldwide. Despite psychotherapies are their treatment of choice, there are difficulties to apply them property in mental health services. Since literature shows that cognitive processes are associated with anxiety and depressive symptoms, more information is needed in order to improve psychological treatments.Aims: To determine the relation between cognitive factors with specific and non-specific emotional disorder symptoms in order to promote the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 110 publications
1
1
0
Order By: Relevance
“…This study had the goal of identifying variables associated with depression and anxiety symptom severity and exemplifying their potential use in clinical assessment through a logistic regression model. The regression model agrees with the results of previous research in that they indicate the value of brooding rumination, pathological worry, and negative metacognitions on uncontrollability or danger as predictors of symptom severity (Corpas et al, 2023;Sun et al, 2017;Taylor & Snyder, 2021): The higher the score on these subscales, the higher the severity of the emotional syndrome (odds ratio [OR] > 1; see Table 6). These outcomes are also in line with the fact that transdiagnostic therapies that include techniques to reduce repetitive negative thinking and restructure metacognitive beliefs are effective in reducing depression and anxiety symptomatology (Carlucci et al, 2021;Newby Variables Associated with Emotional Symptom Severity in Primary Care Patients 7 et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study had the goal of identifying variables associated with depression and anxiety symptom severity and exemplifying their potential use in clinical assessment through a logistic regression model. The regression model agrees with the results of previous research in that they indicate the value of brooding rumination, pathological worry, and negative metacognitions on uncontrollability or danger as predictors of symptom severity (Corpas et al, 2023;Sun et al, 2017;Taylor & Snyder, 2021): The higher the score on these subscales, the higher the severity of the emotional syndrome (odds ratio [OR] > 1; see Table 6). These outcomes are also in line with the fact that transdiagnostic therapies that include techniques to reduce repetitive negative thinking and restructure metacognitive beliefs are effective in reducing depression and anxiety symptomatology (Carlucci et al, 2021;Newby Variables Associated with Emotional Symptom Severity in Primary Care Patients 7 et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Only a few studies have investigated the relationship between any of these strategies and emotional symptoms with primary care patients, and they show an association of rumination with depression (Riihimäki et al, 2016; Talavera et al, 2018). In addition, Corpas et al (2023) found that, although each type of symptoms had a stronger association with a specific cognitive process, rumination, worry, and metacognition were associated with both emotional disorders.…”
mentioning
confidence: 99%